2006
DOI: 10.1021/bi061293x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Investigations of the Pseudouridine Synthase RluA Using RNA Containing 5-Fluorouridine

Abstract: The pseuoduridine synthases (psi synthases) isomerize uridine (U) to pseudouridine (psi) in RNA, and they fall into five families that share very limited sequence similarity but have the same overall fold and active-site architecture, including an essential Asp. The mechanism by which the psi synthases operate remains unknown, and mechanistic work has largely made use of RNA containing 5-fluorouridine (f5U) in place of U. The psi synthase TruA forms a covalent adduct with such RNA, and heat disruption of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(75 citation statements)
references
References 47 publications
6
69
0
Order By: Relevance
“…In response to aberrant processing, improper protein associations, or a lack of post-transcriptional modification, the TRAMP complex polyadenylates noncoding RNA as a prelude to their degradation by Rrp6p and the nuclear exosome (Kadaba et al 2004;LaCava et al 2005;Wyers et al 2005;. Pseudouridylation, the most abundant modification in rRNA, tRNA, and snRNA requires excision and reattachment of uracil by pseudouridylases, and previous studies showed that 5FU strongly inhibits pseudouridylation by some pseudouridylases (Samuelsson 1991; Gu et al 1999;Charette and Gray 2000;Spedaliere and Mueller 2004;Hamilton et al 2006;Reichow et al 2007). Cbf5p catalyzes all pseudouridylation in rRNA and therefore seemed a likely candidate for inhibition by 5FU.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In response to aberrant processing, improper protein associations, or a lack of post-transcriptional modification, the TRAMP complex polyadenylates noncoding RNA as a prelude to their degradation by Rrp6p and the nuclear exosome (Kadaba et al 2004;LaCava et al 2005;Wyers et al 2005;. Pseudouridylation, the most abundant modification in rRNA, tRNA, and snRNA requires excision and reattachment of uracil by pseudouridylases, and previous studies showed that 5FU strongly inhibits pseudouridylation by some pseudouridylases (Samuelsson 1991; Gu et al 1999;Charette and Gray 2000;Spedaliere and Mueller 2004;Hamilton et al 2006;Reichow et al 2007). Cbf5p catalyzes all pseudouridylation in rRNA and therefore seemed a likely candidate for inhibition by 5FU.…”
Section: Resultsmentioning
confidence: 99%
“…Biochemical analyses of the 5FU-inhibited TruA and RluA pseudouridylases showed that the enzymes isomerize 5FU, but form heat-stable adducts with the rearranged products (Gu et al 1999;Hamilton et al 2006). It remains unclear whether these intermediates contain covalent adducts between enzyme and substrate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its synthesis consists of an isomerization of uridine, and is catalyzed by pseudouridine synthases (Pus), a large and ubiquitous group of enzymes that falls into six families, named after their first identified representatives: TruA, TruB, TruD, RsuA, RluA, and Pus10 Gurha and Gupta 2008). The mechanistic details of catalysis, which does not require any cofactors, are subject to renewed interest Hamilton et al 2005Hamilton et al , 2006, as are the structural effects of C on RNA by itself (Helm 2006). During isomerization of uridine to pseudouridine, the carbon-carbon bond of the anomeric ribose-carbon with the carbon 5 of the uracil is formed at the expense of the usual carbon-nitrogen glycosidic bond (Fig.…”
Section: Introductionmentioning
confidence: 99%